Analisis Ketidakpastian Penguasaan Tanah pada Wilayah Pertambangan dalam Perspektif Pasal 1320 KUH Perdata - Fitri Ramadhani; Andini Namira Oktafiandri; Marsya Sari Muzizah; Sumaya Badmas; T. Tohadi (Jurnal Interpretasi Hukum, 2025)
Land acquisition in community mining areas in Jebus District, West Bangka Regency, Bangka Belitung Province is still often carried out without clear legal basis, primarily because agreements are made orally, passed down through generations, or based on social claims without official documentation. This study aims to analyze this phenomenon by assessing its compliance with the legal requirements of agreements as stipulated in Article 1320 of the Civil Code. The method used is a qualitative approach through field studies, which included observation of land acquisition conditions, documentation of boundaries and land use, and interviews with miners, landowners, and village officials. The results indicate that most land acquisition practices do not meet the elements of a verifiable agreement, do not define the object of the agreement with certainty, and are not formalized in a valid agreement, thus failing to meet both formal and material requirements of an agreement. This condition has implications for legal uncertainty, triggering ownership disputes, and weakening the legal standing of the parties. This study concludes that these practices violate Article 1320 and require regulation through legalization of agreements and streamlining of land administration to create legal certainty in land acquisition in community mining areas.